Upaya Pelestarian Budaya Lokal melalui Mata Pelajaran Seni Ukir Jepara di MTs Miftahul Huda Ngasem - Intan Rahmalina; Ahmad Fatah (UNIVERSITAS INDO GLOBAL MANDIRI, 2026)
The preservation of local culture is a strategic effort to ensure the sustainability of cultural heritage so that it remains alive and can be transmitted to future generations. In the educational context, one relevant form of local cultural preservation is through traditional art education, particularly Jepara wood carving art. This study aims to examine the implementation of Jepara wood carving as a subject at MTs Miftahul Huda Ngasem, Batealit District, Jepara Regency, as a medium for preserving local culture amid the challenges of modernization and the declining interest of younger generations in traditional arts. This research employed a descriptive qualitative method with a case study approach. Data were collected through in-depth interviews with the school principal, the wood carving teacher, and students, as well as direct observation of the learning process and documentation of learning activities and students’ wood carving artworks. The findings indicate that: (1) Jepara wood carving instruction is conducted through the introduction of traditional carving techniques, the internalization of cultural values and historical aspects of wood carving, and hands-on practice that enhances students’ skills and appreciation of local culture; (2) Several obstacles were identified, including limited facilities and infrastructure, restricted instructional time, and variations in students’ levels of interest; and (3) Students’ responses to the wood carving subject were generally positive, as reflected in increased interest, active participation, and a growing sense of pride in regional culture. Therefore, the Jepara wood carving subject plays an important role as an effective medium for preserving and developing local culture through formal education